Mycobacterium avium ssp. paratuberculosis and Crohn's Disease-Diagnostic Microbiological Investigations Can Inform New Therapeutic Approaches - John M. Aitken; Jack E. Aitken; Gaurav Agrawal (MDPI AG, 2024)
Mycobacterium avium ssp. paratuberculosis (MAP) is the cause of Johne's disease (JD), which is a chronic infectious gastrointestinal disease of ruminants and is often fatal. In humans, MAP has been associated with Crohn's disease (CD) for over a century, without conclusive evidence of pathogenicity. Numerous researchers have contributed to the subject, but there is still a need for evidence of the causation of CD by MAP. An infectious aetiology in CD that is attributable to MAP can only be proven by bacteriological investigations. There is an urgency in resolving this question due to the rising global incidence rates of CD. Recent papers have indicated the "therapeutic ceiling" may be close in the development of new biologics. Clinical trial outcomes have demonstrated mild or inconsistent improvements in therapeutic interventions over the last decades when compared with placebo. The necessity to revisit therapeutic options for CD is becoming more urgent and a renewed focus on causation is essential for progress in identifying new treatment options. This manuscript discusses newer interventions, such as vaccination, FMT, dietary remediation and gut microbiome regulation, that will become more relevant as existing therapeutic options expire. Revisiting the MAP theory as a potential infectious cause of CD, rather than the prevailing concept of an "aberrant immune response" will require expanding the current therapeutic programme to include potential new alternatives, and combinations of existing treatments. To advance research on MAP in humans, it is essential for microbiologists and medical scientists to microscopically detect CWDM and to biologically amplify the growth by directed culture.